Intelligent routing information protocol using full triggered update mechanism - Gani, Abdullah; Hassan, M.K.; Zaidan, A.A.; Zaidan, B.B. (Academic Journals, 2011)
The heartbeat of network is the routing services which are available upon the execution of protocols. Many routing protocols emerge over one another to strive for betterment in performing the main function of routing the packets to destination efficiently. Despite the superiority of the new protocols in certain feature, the old routing information protocol (RIP) is still widely used due to its simplicity. RIP updates its routing table on a constant interval period by checking the existence of neighbor nodes and changes on the path availability. This mechanism, however, has some drawbacks of bandwidth consumption and higher routing overhead generation. This paper studies the affect of periodic update mechanism on the consumption of bandwidth and proposes a new routing update mechanism. Our technique eliminates the periodic update mechanism in RIP and replaces it with full triggered update by topology change detection mechanism (TRIP). The proposed mechanism triggers the update when topology change is detected. We tested our proposed mechanism in Network Simulator 2 (Ns 2) simulations. The results show that TRIP consumes less bandwidth and sends less routing packets by 70 than RIP. This work contributes significantly to small network as bandwidth is obviously limited.